(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Medication wastage in household describes any medicine which are not consumed by the patient and remains unused leading to expiry and also includes medicines which loses its therapeutic value due to damage due to improper storage condition or improper handling. The aim of the present study was to find out the extent and reason behind the medication wastage in families in Goa (India). Study was carried out using door to door cross sectional survey adopting snowball sampling method. 250 households from five major cities of Goa were surveyed using questionnaire. It was observed that mean (SD) family size of Goan household was 3.76(1.23) members. It was revealed in the survey that 59% of the families procured medicines from the nearby pharmacy. Most common medicine stored in the household were analgesic/ antipyretic drugs (17%) mean (SD) 2.67 (1.76). 16% of the medicine stored in the household were expired, whereas 22% remained unused.18% of the people stopped the medication after resolving the symptoms and thus did not take the complete prescribed dosage, whereas 12% of the people stopped the medication after experiencing side effects. Families having children as well as elderly member tend to stock more medicine 24.69(2.01). It was found that level of education is directly proportional to the amount of storage of medicine. Head of the family who were graduate, post graduate tend to store more medicine having mean (SD) 13.21(1.12) and 15.11(1.36) respectively. Financially stable families tend to store more medicine 15.37 (0.96). Medicine wastage is serious issue in Goan families and can be reduced by proper patient counselling and awareness.